Morphology, growth, and physiological traits of greenhouse cucumber seedlings as affected by supplementary white and blue LEDs - Yan, Zhengnan; Wang, Long; Cheng, Jie; Lin, Duo; Yang, Yanjie (International Journal of Agricultural and Biological Engineering, 2022)
Supplemental lighting can be applied in the greenhouse to obtain high-quality seedlings when the solar daily light integral (DLI) is insufficient. However, there is no optimal strategy for the supplementary light provided by white and blue light-emitting diodes (LEDs) with the same DLI in cucumber (Cucumis sativus L.) seedling production grown in the greenhouse in early spring. The objective of the study was to determine changes in morphology, photosynthesis, growth, and physiological characteristics in greenhouse-grown cucumber seedlings (cv. Tianjiao No. 5) depending on different supplementary fractions (28.5%, 33.5%, 38.5%, 43.5%, and 48.5%) of blue light (B) under constant DLI provided by combinations of white (B28.5% included) and blue LEDs, and cucumber seedlings were grown with sunlight only were set as the control. The results documented that supplementary light resulted in compact and robust greenhouse-grown cucumber seedlings with higher chlorophyll content and net photosynthetic rate compared to those grown without supplementary light. The plant height and hypocotyl length of cucumber seedlings decreased quadratically with an increase of blue light fractions provided by combinations of white and blue LEDs. Additionally, the leaf area and stem diameter of cucumber seedlings increased first and a decreased trend was observed subsequently with the increasing fraction of blue light in a quadratic function. Similar trends were found in root architecture (e.g., root length, root surface area, and root volume) and root activity of cucumber seedlings; however, no significant differences were exhibited as blue light fraction increased from 38.5% to 43.5% provided by supplementary light. Stem firmness and cellulose content increased by 26.2% and 23.4%, respectively, as 15% blue light was added to white LEDs. In conclusion, the 43.5% blue light created by supplementary broad-spectrum white and blue LEDs resulted in compact and stoutest cucumber seedlings along with well-developed root system and higher stem firmness, thus improving the mechanical strength of the greenhouse-grown cucumber seedlings for transplanting.Keywords: blue light, hypocotyl length, photosynthetic capacity, stem firmness, supplementary lightDOI: 10.25165/j.ijabe.20221506.7351Citation: Yan Z N, Wang L, Cheng J, Lin D, Yang Y J. Morphology, growth, and physiological traits of greenhouse cucumber seedlings as affected by supplementary white and blue LEDs. Int J Agric & Biol Eng, 2022; 15(6): 60–66.